Lattice groups - Kurdachenko, L.A.; Yashchuk, V.S.; Subbotin, I.Y. (Algebra and Discrete Mathematics, 2015)
In this paper, we introduce some algebraic structure associated with groups and lattices. This structure is a semigroup and it appeared as the result of our new approach to the fuzzy groups and L-fuzzy groups where L is a lattice. This approach allows us to employ more convenient language of algebraic structures instead of currently accepted language of functions.